Representation of the Indonesian Tax Amnesty Program in the Jakarta Post Online Articles: A Macrostructure Analysis - Fathin Shofaa (Passage, 2017)
The present research seeks to examine the representation of the Indonesian Tax Amnesty Program in the Jakarta Post online news articles in terms of macrostructure analysis as well as unveil the underlying ideology of the Jakarta Post with regard to the issue. This research employs a qualitative method by relying on the sociocognitive approach to Critical Discourse Analysis (van Dijk, 2009) to conduct the semantic macrostructure analysis and interpret the results. The data used in this research include ten articles from the Jakarta Post. Through the application of macrorules analysis, there are ten macropropositions derived from the selected articles. The macropropositions are, then, analysed to further examine the representation. It is revealed that the Indonesian Tax Amnesty Program is mostly represented positively in the Jakarta Post. Out of the ten macropropositions, 80% indicate positive representation and 20% indicate neutral representation of the issue. No negative representation is found. Furthermore, it is found that in terms of ideology, the Jakarta Post tends to adhere to capitalism.Keywords: critical discourse analysis, macrostructures, news articles, representation, ideology, tax amnesty program